Pleural effusion: a structured approach to care. - Rahman, N; Chapman, S; Davies, R (2004)
The accumulation of fluid in the pleural space is a common manifestation of a wide range of disease. This review provides a structured approach to the investigation of the patient with a pleural effusion. This should allow an accurate diagnosis to be made with the minimum number of invasive and time-consuming investigations.